2013
DOI: 10.2135/cropsci2013.03.0136
|View full text |Cite
|
Sign up to set email alerts
|

Maize Physiological Responses to Heat Stress and Hormonal Plant Growth Regulators Related to Ethylene Metabolism

Abstract: Hormonal plant growth regulators (HPGRs) have been evaluated in field grown maize (Zea mays L.), but never as a tool for prevention or mitigation of heat stress. We analyzed grain yield determination of maize crops exposed to contrasting temperature regimes (nonheated control plots [TC]; heated plots [TH]) and the application of HPGRs associated with ethylene metabolism (ethephon [ETH]; MCP [1‐MCP]). Heating extended over daytime hours between V11 and tasseling (VT), and products were sprayed immediately befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Therefore, the mechanism by which inferior kernels switch from weight reduction to abortion may involve sugar signaling ( Kakumanu et al , 2012 ). To this end, ethylene has been suggested to be involved in ovary abortion in maize and wheat ( Young et al , 1997 ; Young and Gallie, 1999 ; Hays et al , 2007 ; Cicchino et al , 2013 ). Glucose could play a vital role in suppressing ethylene biosynthesis ( Hong et al , 2004 ; Wang et al , 2014 ) and its signaling pathway ( Yanagisawa et al , 2003 ; Iqbal et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mechanism by which inferior kernels switch from weight reduction to abortion may involve sugar signaling ( Kakumanu et al , 2012 ). To this end, ethylene has been suggested to be involved in ovary abortion in maize and wheat ( Young et al , 1997 ; Young and Gallie, 1999 ; Hays et al , 2007 ; Cicchino et al , 2013 ). Glucose could play a vital role in suppressing ethylene biosynthesis ( Hong et al , 2004 ; Wang et al , 2014 ) and its signaling pathway ( Yanagisawa et al , 2003 ; Iqbal et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of heat stress and subsequent ET production has been investigated in multiple reproductive tissues including pollen grains (Firon et al 2012), anthers (Jegadeesan et al 2018a, stigma/style, ovaries (Savada et al 2017), flowers (Jegadeesan et al 2018b, kernels (Cicchino et al 2013), developing grains (Dias et al 2010), and fruits (Alba et al 2005;Ketsa et al 1999). While the majority of the studies showed a positive role of ET in heat stress tolerance, a few highlighted a negative interaction between ET and heat stress tolerance.…”
Section: Heat Stress-induced Ethylene Production In the Reproductive Tissuesmentioning
confidence: 99%
“…While the majority of the studies showed a positive role of ET in heat stress tolerance, a few highlighted a negative interaction between ET and heat stress tolerance. For example, exogenous application of ET biosynthesis inhibitor improved grain weight under heat stress conditions in wheat (Hays et al 2007), while exogenous treatment of ET releasing compound ethephon showed beneficial results in terms of kernel set and grain yield during heat stress conditions in maize (Cicchino et al 2013).…”
Section: Heat Stress-induced Ethylene Production In the Reproductive Tissuesmentioning
confidence: 99%
“…The likelihood of mitigations through using plant growth regulators (Cicchino et al, 2013), or adequate management of magnesium (Mengutay et al, 2013) are being discussed. Around the world, food production increased linearly with the increment of N use in the agricultural systems (Tilman, 1999), and N fertilisation is likely one of the most common management practices implemented in maize production worldwide.…”
Section: Introductionmentioning
confidence: 99%